2013
DOI: 10.1364/ol.38.001942
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 8 nJ pulses from a dissipative-soliton fiber laser with a nonlinear optical loop mirror

Abstract: Theoretical and experimental investigations of the behavior of normal-dispersion fiber lasers with nonlinear-optical loop mirrors are presented. The use of a loop mirror causes the laser to generate relatively long, flat-topped pulses. The pulse energy can be high, but the pulse duration is limited to greater than 300 fs. Experimentally, 8-nJ pulses that can be dechirped to 340 fs duration are obtained. The laser is a step toward an all-fiber, environmentally-stable design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…al. reported pulses well consistent with the DSR, which we believed, based on our model were due to a large splitting ratio thus a small saturation power of the NOLM [28]. By simply increasing the loop length, saturation power can also be reduced.…”
Section: B Case For Sinusoidal Sa Curvesupporting
confidence: 83%
See 1 more Smart Citation
“…al. reported pulses well consistent with the DSR, which we believed, based on our model were due to a large splitting ratio thus a small saturation power of the NOLM [28]. By simply increasing the loop length, saturation power can also be reduced.…”
Section: B Case For Sinusoidal Sa Curvesupporting
confidence: 83%
“…Although we focus on the qualitative analysis on DSR generation, we believe our results are practical for experiments. As a result of this work, a method to achieve DSR in practice is suggested [28], [29]: inducing strong peak-power-clamping effect, for example, using a very long NOLM as the mode-locking technique. Our numerical results further shows that under DSR generation, the generated pulse peak power can be directly controlled by the cavity peak-power-clamping effect, which is also demonstrated experimently.…”
Section: Discussionmentioning
confidence: 99%
“…These values are comparable to those for the B10-nJ SRS-free DS generated in all-fibre configurations of Yb-doped fibre oscillators (for example, ref. 25) and only slightly worse than the best results for the B3-nJ Er-doped fibre oscillators 26 . In our case, the total pulse energy at the DS and RDS outputs is 25 nJ, with nearly equal division inside the cavity and a fourfold difference at the outputs because of selective DS amplification.…”
Section: Resultsmentioning
confidence: 83%
“…The transmission of the NOLM can be modified by changing the loop length, coupler split ratio and incoming pulse intensity 13 . Zhao et al reported on 8 nJ pulses that could be compressed below 300 fs from an all-fiber oscillator with the NOLM mode-locker 14 . Although impressive, the design was not fully environmentally stable because of use of non-PM fibers.…”
Section: Mode-locking Methodsmentioning
confidence: 99%